Mobile telecommunications infrastructure and economic growth: Evidence from China - Michael R. Ward; Shilin Zheng (International Telecommunications Society (ITS), 2014)
We contribute to the role of telecommunications infrastructure on economic growth in three ways. We separately examine fixed-line and mobile telephone subscription levels. We compare results across periods and regions that differ by the level of development. In addition, we develop a method designed to address endogeneity of telecommunications with respect to growth. We find that mobile services contribute much more to growth but that the effect diminishes as the provincial economy develops more.
Keywords: O4; L96; 330; Growth; Mobile Phone; China